2003
DOI: 10.1042/bj20021193
|View full text |Cite
|
Sign up to set email alerts
|

New enzyme belonging to the family of molybdenum-free nitrate reductases

Abstract: A novel molybdenum-free nitrate reductase was isolated from the obligate chemolithoautotrophic and facultative anaerobic, (halo)alkaliphilic sulphur-oxidizing bacterium Thioalkalivibrio nitratireducens strain ALEN 2. The enzyme was found to contain vanadium and haem c as cofactors. Its native molecular mass was determined as 195 kDa, and the enzyme consists of four identical subunits with apparent molecular masses of 57 kDa. Apart from nitrate, the enzyme can utilize nitrite, chlorate, bromate, selenate and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
(24 reference statements)
2
33
0
Order By: Relevance
“…X-ray diffraction studies show the Schiff base pyr 2 The complexes prepared are slightly soluble in water and the order of stability of the complexes formed is pyridoxamine < H 2 pyr 2 en < H 2 Rpyr 2 en. Pyridoxal and pyridoxamine are forms of vitamin B 6 and are nontoxic metabolites. Their vanadium complexes may therefore be good candidates for therapeutic use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…X-ray diffraction studies show the Schiff base pyr 2 The complexes prepared are slightly soluble in water and the order of stability of the complexes formed is pyridoxamine < H 2 pyr 2 en < H 2 Rpyr 2 en. Pyridoxal and pyridoxamine are forms of vitamin B 6 and are nontoxic metabolites. Their vanadium complexes may therefore be good candidates for therapeutic use.…”
Section: Resultsmentioning
confidence: 99%
“…T h e H 2 pyr 2 en and H 2 Rpyr 2 en ligands contain six protons that dissociate in the measurable pH range, so the totally protonated species correspond to [H 6 . The corresponding protonation constants are included in Table 3.…”
Section: Ligand Protonation By Ph-potentiometry and 1 H Nmr Spectroscmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that strain ALEN 2 T possesses both nitrate and nitrite reductase activities despite the fact that it is unable to use nitrite as an electron acceptor in vivo. Antipov et al (2003) have demonstrated the presence of a nitrate/nitrite reductase in strain ALEN 2 T with unusual properties. Activities of the sulfur-metabolizing enzymes thiosulfate reductase, sulfite dehydrogenase and sulfide dehydrogenase were found in the soluble fraction of cell-free extract of strain ALEN 2 T at pH 10 [690, 260 and 60 nmol (mg protein) 21 min 21 , respectively].…”
mentioning
confidence: 99%